Post-bureaucratic model and organizational performance in the Nigerian public service - Irikefe Afonughe; Aboribo Roy Ochuko (Qualitative Research of Business and Social Sciences, 2025)
This paper examines the implementation of the post-bureaucratic model and its impact on organizational effectiveness within the Nigerian public sector. The primary mandate of the public service in Nigeria is to ensure optimal performance in delivering a broad spectrum of services to the general public. However, the sector is frequently constrained by a broad range of responsibilities, a large population to serve, and the need for strict adherence to established regulations, all of which collectively impede operational efficiency. Thus, the Nigerian public service continues to operate under intense institutional pressure. This condition has historically legitimized the adoption of bureaucratic structures to ensure procedural precision and minimize the risk of litigation by dissatisfied stakeholders. Nonetheless, the advent of advanced technologies has rendered many traditional bureaucratic paradigms increasingly inadequate for addressing contemporary organizational demands. In response, this article examines the effectiveness of the post-bureaucratic model as a strategic approach for improving organizational performance within Nigeria’s public sector. Anchored in a qualitative research design, the study draws upon secondary data obtained from scholarly texts, peer-reviewed journal articles, reputable online sources, and media publications. Key findings highlight persistent bureaucratic impediments, including red tape, administrative inertia, corruption, and structural rigidity. The study concludes by proposing context-specific strategies for embedding post-bureaucratic practices within the Nigerian public service. Central among these are the prioritization of leadership development, the formulation of robust change management frameworks, and the adoption of policy instruments that incentivize innovation.  The study contributes to knowledge by demonstrating the significance of the post-bureaucratic paradigm in improving organizational performance in Nigeria's public service.